KAJIAN SOSIOLOGI HUKUM TERHADAP PENYALAHGUNAAN NARKOTIKA OLEH ANAK - wahyu Rasyid (FAKULTAS HUKUM UM PAREPARE, 2017)
The aim of this research is to know (1) Efforts to prevent abuse of narcotics by children and to know (2) Factors influencing the effort of prevention of narcotics abuse by children. (3) Community participation in prevention of narcotics abuse by children. This research was conducted in Makassar District Court, Makassar City area. This type of research is empirical research with the approach of legal sociology. Types of data consisting of primary data and secondary data obtained through interviews and analyzed and then presented in the form of descriptive. The results showed that (1) Efforts to prevent abuse of narcotics by children in the city of Makassar has been running, but not yet effective, it is known from the number of children who abuse drugs continue to increase both in quality and quantity from year to year other than that harmonization apparatus law and community participation is still not optimal, so the results are not yet realized. (2) Factors affecting the effectiveness of worldviews and efforts of penal oriented, public understanding and perception about the dangers of narcotics abuse by children are minimal, and the level of public confidence in the legal apparatus is still low, the availability of supporting facilities and infrastructure is limited. (3) The lack of optimal participation of the community is caused by the working relationship of the law enforcement apparatus with the community has not been running well.